Comparative analysis of thermal aging behavior and comprehensive performance of high viscosity asphalt (HVA) from cohesion, adhesion and rheology perspectives. (24th January 2022) - Yang, Jianhua; Zhang, Zhengqi; Shi, Jierong; Yang, Xinhong; Fang, Ying
Highlights: Thermal aging behavior of HVA was contrastively explored from cohesion, adhesion and rheology perspectives. Variations of phase topography and functional groups of HVA under aging were investigated using AFM and FTIR tests. Correlation between macro-micro indicators of asphalts under aging was analyzed according to grey correlation theory. Aging weakened cohesion, adhesion and low-temperature property of HVA and diminished its surface roughness. Surface roughness Ra and functional group indexes correlated well with several macro indexes. Abstract: High viscosity asphalt (HVA) has been widely utilized in the paving of large-void asphalt pavement, and it will be affected by thermal aging and exhibit different pavement performance. In this study, through a series of macroscopic and microscopic experiments, the change behaviors of cohesion, adhesion, high- and low-temperature rheological properties, microscopic phase structure and functional groups of HVA under different thermal aging conditions were first analyzed—in comparison with the three asphalts viz. styrene-butadienestyrene (SBS) modified asphalt (SBSMA), crumb rubber modified asphalt (CRMA) and neat asphalt (NA). Further, the relationship between macro-micro properties of asphalt binders was investigated by grey correlation theory, and the comprehensive performance of HVA at different aging stages and its aging resistance were contrastively evaluated via using radar chart analysis method. Results showed that aging degraded the cohesion and adhesion of asphalt binders as well as the water stability of asphalt-aggregate systems, and weakened the low-temperature property of asphalt binders—compared to the unaged sample, the short- and long-term aging reduced the cohesion work of HVA by 1.10% and 3.41%, respectively, and decreased the water stability index of HVA-limestone system by 0.54% and 1.86%, respectively. However, the variations of viscoelastic properties, temperature sensitivity, creep recovery ability and rutting resistance of HVA under aging were inconsistent with those of SBSMA, CRMA and NA. Aging decreased the microscopic surface roughness Ra of HVA and altered the intensity of functional groups at different wavenumbers, and the short- and long-term aging diminished its Ra by 21.26% and 37.85% compared to the unaged sample, respectively. Grey correlation analysis showed that the microscopic surface roughness Ra and the functional group indexes at different wavenumbers correlated well with several macroscopic indexes, which successfully explicated the variations of macroscopic properties of HVA from the micro perspective. Radar chart analysis displayed that the comprehensive performance of HVA in the original and short-term aging stages was second only to CRMA, but its comprehensive performance after long-term aging was only superior to NA; overall, HVA exhibited the most favorable anti-aging performance.